RCEP & WGEC: Boosting Indonesia’s E-Commerce and Attracting China’s Investment - Mohammad Rayyan (Dinasti Research, 2025)
In the era of globalization and revolution 4.0, the economic and trade aspects of a country cannot be separated from progress. Currently, many countries are developing their economies with technology-based trading activities (e-commerce). China is a country with a fairly large development of the e-commerce industry and generates significant revenue in the e-commerce sector. Indonesia as a developing country is considered to have become a country in the Southeast Asia region that has progress in the development of the e-commerce industry. Seeing this opportunity, China initiated the formation of The Regional Comprehensive Economic Partnership (RCEP) and formed a Working Group on E-Commerce (WGEC) to enhance the development of the e-commerce industry in Indonesia. Meanwhile, Indonesia has an interest in developing the e-commerce industry and is determined to become a major player in the e-commerce industry in the Southeast Asian region as a country. This study will use the concept of economic nationalism to analyze the cooperation between Indonesia and China in e-commerce cooperation. carried out through the WEGC framework, the two countries certainly provide benefits and also each country can fulfill its national needs in this cooperation.